2018
DOI: 10.17759/cpp.2018260304
|View full text |Cite
|
Sign up to set email alerts
|

The Generalized Problematic Internet Use Scale 3 Modified Version: Approbation and Validation on the Russian Sample

Abstract: The present study introduces the third version of the Generalized Problematic Internet Use Scale which takes into account the current tendencies in internet use and is based on the second revised version of the scale (GPIUS2, Caplan, 2010). The research was carried out online among Android OS users. The factor structure was verified on a sample of 204 persons (102 males and 102 females) aged from 14 to 21 years (M=17,34; SD=2). Convergent and intercorrelation validity was verified on samples of 1100 and 707 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In our research, adolescents who were part of the cluster I, as opposed to the cluster II individuals, also have more pronounced withdrawal symptoms (Wit), which reflects a sense of discomfort in the absence of access to Internet resources [31], regardless of the presence or absence of Internet-addicted behavior. The correlations between the Wit score and HRV parameters reflect the tension of cardiac activity and a decrease in vagal reserves of autonomous regulation of the heart rate, in conjunction with an increase in the severity of withdrawal symptoms in the absence of access to Internet resources.…”
Section: Discussionmentioning
confidence: 55%
“…In our research, adolescents who were part of the cluster I, as opposed to the cluster II individuals, also have more pronounced withdrawal symptoms (Wit), which reflects a sense of discomfort in the absence of access to Internet resources [31], regardless of the presence or absence of Internet-addicted behavior. The correlations between the Wit score and HRV parameters reflect the tension of cardiac activity and a decrease in vagal reserves of autonomous regulation of the heart rate, in conjunction with an increase in the severity of withdrawal symptoms in the absence of access to Internet resources.…”
Section: Discussionmentioning
confidence: 55%
“…Long periods of Internet use also became much more frequent. The study showed that female sex, age, depression and stress had an authentic correlation with total scores of Internet addiction; it was also noted that prevalence of depression, anxiety and stress with variable intensity correlated authentically with groups of addicted Internet users, problematic Internet users and adequate Internet users [19,20].…”
mentioning
confidence: 99%